USING MEDICAL TERMINOLOGY IN TEACHING VOCABULARY AS AN AUTHENTIC MATERIAL AT PHARMACY DEPARTMENT OF SMK KEPERAWATAN GAFUR YAHYA PALOPO - Jumharia, Djamereng; Restu, Restu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
The objective of this research was to find out the effectiveness of using medical terminology in teaching vocabulary as an authentic material at Pharmacy Department at the second year students of SMK Keperawatan  Gafur Yahya Palopo. This research was pre experimental research with pre test and post test design. The population was the pharmacy department students which consists of two classes with total number was 60.  This research used purposive sampling from population. There were 30 students from class A were chosen as sample since the class have low interest in learning in compare to class B.  This research used vocabulary test as instrument.  In collecting data, this research used some procedures namely pre test, treatment, post test. In pre test and post test used vocabulary test.  In pre test the students got mean score 6.05.  This is implies that the students had low vocabulary.  In post test, the students got mean score 9.05 in very good classifications. This is implies that the students got increasing in vocabulary after treatment.  Based on the findings and discussion of the study, the writer concludes that the use of medical terminology is effective authentic material  in teaching vocabulary to the students at Pharmacy Department of SMK Keperawatan Gafur Yahya Palopo.USING MEDICAL TERMINOLOGY IN TEACHING VOCABULARY AS AN AUTHENTIC MATERIAL  AT PHARMACY DEPARTMENT OF SMK KEPERAWATAN GAFUR YAHYA PALOPO